Prevalence of Newborn Intensive Care Unit-Acquired, Healthcare-Associated Blood-Stream Infections in Neonatal Intensive Care Unit Patients: Results From The First National Point-Prevalence Survey - (:unkn) unknown (CUKUROVA UNIV, FAC MEDICINE, 2015)
Purpose: Patients admitted to neonatal intensive care units (NICUs) are at high risk of Healthcare-Associated Bloodstream Infection (HABSI). We conducted a national multicenter assessment of HABSI in NICUs to determine the prevalence of infections and describe associated risk factors. Material and Methods: We conducted a point prevalence survey of HABSI in 38 NICUs. Patients present on the survey date were included. Data on demographics, underlying diagnoses, therapeutic interventions/treatments, infections, and outcomes were collected for all NICU patients. Results: A total of 933 patients in 38 NICUs participated in the study, 142 of whom had HABSI, corresponding to a prevalence of 15.2%. The reported HABSI were clinical sepsis (n=88, 61.9%), laboratory-confirmed bloodstream infection (n=50, 35.2%) and catheter related infection (n=4, 2.9%). Causative microorganisms were isolated in 54 (38%) patients with HABSI. The most common causative pathogens were coagulase negative Staphylococcus (n=34, 25.7%) and Candida spp. (n=10, 7%). The risk factors for HABSI were total parenteral nutrition, nasogastric feeding tube, central venous catheter, absence of High Efficiency Particulate Air (HEPA), gastrointestinal system disease, carrying out the preventive application bundle for catheter related infections, absence of next to each incubator disinfectant, duration of hospitalization more than 3 days and post-natal age more than 30 days. At 4-week follow up, 33 (3.5%) patients had died, 13 (39.3%) of whom died from healthcare-associated infections. HABSI were not found to be risk factors for death (p>0.05). Conclusion: This national multicenter study documented the high prevalence of NICU-acquired infections. Preventing these infections should be national priority.
Keywords: Infection; Infection Control; Newborn; Newborn Intensive Care Units; NOSOCOMIAL INFECTIONS; RISK-FACTORS; SURVEILLANCE